Metabolic utilization of human osteoblast cell line hFOB 1.19 under normoxic and hypoxic conditions: a phenotypic microarray analysis - Cui, Yan Chao; Qiu, Yu Sheng; Wu, Qiong; Bu, Gang; Peli, Amira; Teh, Seoh Wei; Ang, Kok Pian; Ms Joseph, Narcisse; Koh, Avin Ee-Hwan; Farhana, Aisha; Alzahrani, Badr; Khan, Mohammed Safwan Ali; et al. (Sage Publications, 2021)
Osteoblasts play an important role in bone regeneration and repair. The hypoxia condition in bone occurs when bone undergoes fracture, and this will trigger a series of biochemical and mechanical changes to enable bone repair. Hence, it is interesting to observe the metabolites and metabolism changes when osteoblasts are exposed to hypoxic condition. This study has looked into the response of human osteoblast hFOB 1.19 under normoxic and hypoxic conditions by observing the cell growth and utilization of metabolites via Phenotype MicroArrays™ under these two different oxygen concentrations. The cell growth of hFOB 1.19 under hypoxic condition showed better growth compared to hFOB 1.19 under normal condition. In this study, osteoblast used glycolysis as the main pathway to produce energy as hFOB 1.19 in both hypoxic and normoxic conditions showed cell growth in well containing dextrin, glycogen, maltotriose, D-maltose, D-glucose-6-phospate, D-glucose, D-mannose, D-Turanose, D-fructose-6-phosphate, D-galactose, uridine, adenosine, inosine and α-keto-glutaric acid. In hypoxia, the cells have utilized additional metabolites such as α-D-glucose-1-phosphate and D-fructose, indicating possible activation of glycogen synthesis and glycogenolysis to metabolize α-D-glucose-1-phosphate. Meanwhile, during normoxia, D-L-α-glycerol phosphate was used, and this implies that the osteoblast may use glycerol-3-phosphate shuttle and oxidative phosphorylation to metabolize glycerol-3-phosphate.